Analisis Kekuatan Rangka Mesin Padi Menggunakan Software Solidwork 2022 - Dafa Intifada; Reza Setiawan; Iman Dirja (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Strength analysis of rice machine frames using SolidWorks 2022 software is a study that aims to evaluate the structural strength of rice machine frames using computer simulation methods. SolidWorks 2022 is used as a platform to perform strength analysis by considering the operational loads applied to the machine during the use process. This research involved detailed 3D modeling of the rice machine frame and load simulations to predict its structural response. Factors such as load distribution, torque, and forces applied to various parts of the frame are explored to understand potential points of failure or deformation that may occur. The analysis results are expected to provide insight into the structural integrity of the rice machine frame in the face of different operational conditions. By utilizing SolidWorks 2022 technology, this research also aims to improve the overall rice machine design, increase operational efficiency, and reduce the risk of failure which can affect machine performance and reliability in the field